STUDY ON MARKET PROCESS OF TUNA POLE-AND-LINE FISHERY IN EASTERN INDONESIA: A STUDY CASE IN SORONG, PAPUA BARAT PROVINCE - Alexander M.A Khan; Lantun P. Dewanti; Izza M. Apriliani; Dedi Supriadi; Anta M. Nasution; Tim S. Gray; Aileen C. Mill; Nicholas V. C. Polunin (Research Center for Fisheries, 2020)
This research is a study of the way the small-scale pole-and-line tuna fishery in Sorong, Indonesia by examining official records of supply chains; key informant and fishers’ perceptions of marketing; and personal observations of landings and selling. The main finding of the study is that the pole-and-line fishers in Sorong have made strenuous efforts to escape the constrictions of middlemen by direct selling to processors.